University Students’ Responses to Fake News on Social Media - Binh, Ha Anh; Thanh, Nguyen Quy; Oanh, Lu Thi Mai (VNU Journal of Science: Education Research; Vol 41 No 4, 2025)
This study examines how university students receive and respond to unverified information on social media, focusing on behaviors such as acceptance, verification, sharing, and passive reception. Applying the Dual-Process Theory, the findings suggest that students often rely on heuristic processing, meaning they tend to believe or ignore information based on its familiarity, popularity, or emotional appeal. The results also indicate that while many students believe they can detect fake news, their actual fact-checking behaviors are inconsistent. A significant portion of respondents admitted to having shared unverified information, while others simply received it passively without any response. This reveals a notable gap between skepticism and active verification. Therefore, there is a need for media literacy education programs and accuracy-focused interventions to encourage systematic information processing and reduce the risk of fake news dissemination among students.